Therapeutic Applications of Mesenchymal Stem Cells in Veterinary Medicine - Gugjoo, Mudasir Bashir (Singapore : Springer Nature Singapore : Imprint: Springer, 2022)
This book reviews the potential therapeutic and reproductive applications of mesenchymal stem cells in veterinary regenerative and reproductive medicine. The systemic approach focuses on musculoskeletal structures like cartilage, bone, muscle, tendon, ligaments and nervous tissues. It also focuses on other body systems like gastrointestinal, cardiovascular, urogenital, respiratory and integumentary system. Besides, the special glands or organs like endocrine glands and eye and its adnexa are also focused. The book chapters discusses the problems and the need for regenerative medicine employing MSCs. It provides an ex vivo basis of MSCs therapeutics and reproductive potential followed by their in vivo applications. The book further provides an understanding on the behavior and mechanisms of action of mesenchymal stem cells. The book also abridges challenges and provides future prospects of mesenchymal stem cells in clinical and reproductive applications. As such, the book offers a valuable resource for students, veterinarians, and scientists working in the regenerative and reproductive sciences in human and veterinary medicine.
Chapter 1: Mesenchymal stem cells therapeutic applications in cartilage regeneration -- Chapter 2: Mesenchymal stem cells therapeutic applications in bone regeneration -- Chapter 3: Mesenchymal stem cells therapeutic applications in muscle, tendon and ligament regeneration -- Chapter 4: Mesenchymal stem cells therapeutic applications in peripheral nervous system disorders -- Chapter 5: Mesenchymal stem cells therapeutic applications in central nervous system disorders -- Chapter 6: Mesenchymal stem cells therapeutic applications in cardiovascular disorders -- Chapter 7: Mesenchymal stem cells therapeutic applications in gastrointestinal disorders -- Chapter 8: Mesenchymal stem cells therapeutic applications in lung disorders -- Chapter 9: Mesenchymal stem cells in reproductive system: reproductive and therapeutic applications -- Chapter 10: Mesenchymal stem cells therapeutic applications in urinary system disorders -- Chapter 11: Mesenchymal stem cells therapeutic applications in integumentary system disorders -- Chapter 12: Mesenchymal stem cells therapeutic applications in endocrine disorders -- Chapter 13: Mesenchymal stem cells therapeutic applications in eye and adnexa ailments.
Keywords: Veterinary medicine; Stem cells; Veterinary Science; Veterinary Clinical Medicine; Stem Cell Biology